2020
DOI: 10.3390/nano10122564
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve the Properties of Amaranth Protein Isolate-Based Thin Films for Food Packaging Applications: Nano-Layering through Spin-Coating and Incorporation of Cellulose Nanocrystals

Abstract: In this work, two different strategies for the development of amaranth protein isolate (API)-based films were evaluated. In the first strategy, ultrathin films were produced through spin-coating nanolayering, and the effects of protein concentration in the spin coating solution, rotational speed, and number of layers deposited on the properties of the films were evaluated. In the second strategy, cellulose nanocrystals (CNCs) were incorporated through a casting methodology. The morphology, optical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…López-Rubio et al . ( 46 ) found that nanoreinforcement depends on the amount of particles. The increase in the content of the particles causes them to self-aggregate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…López-Rubio et al . ( 46 ) found that nanoreinforcement depends on the amount of particles. The increase in the content of the particles causes them to self-aggregate.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of more nanoparticles in the matrix led to an agglomeration, and thus the TS decreases. López-Rubio et al (46) found that nano reinforcement is dependent on the concentration of particles. The increase in the Please note that this is an unedited version of the manuscript that has been accepted for publication.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Hence, other plant proteins from rice and peas were used in packaging than the allergic proteinaceous source (Hadidi et al, 2022). Research done by Lόpez‐Rubio et al (2020), reinforced nanocellulose (5%–20%) in amaranth protein isolate polymer matrix proved that the added cellulose increased the mechanical properties of the film. One of the significant limitations of protein films is their poor mechanical strength; this issue can be rectified with the addition of cellulose.…”
Section: Application and Characteristics Of Bnc‐based Packagingmentioning
confidence: 99%
“…For nanofiller biodegradable composites, nanofiller orientation and dispersion uniformity in the polymer matrix play an important role in its barrier properties [115]. Diffusion pathway of fluids such as water or oil is longer and follows an irregular curve route, thus decreasing permeability of nanocomposites [116].…”
Section: Barrier Propertiesmentioning
confidence: 99%